Relasi Kuasa Dokter Kepada Pasien di Klinik Kecantikan Naavagreen Natural Skincare Kotabaru Yogyakarta - Juli Natalia Silalahi (Equilibrium: Jurnal Pendidikan, 2022)
Beautiful construction designed by various entities, including Naavagreen Natural Skincare Kotabaru, Yogyakarta. Naavagreen offers patients that is natural beauty, quality, cheap and reliable for all customers. This condition makes the public trust in Naavagreen skincare (Paransih, 2017). Naavagreen patients are willing to put aside their salary, time for treatment at Naavagreen, and even let their skin and face be treated by Naavagreen to get a beautiful concept as constructed by Naavagreen. Patient trust is based on Naavagreen designed like a legitimate hospital room, this condition further strengthens Naavagreen patients for treatment. The patient has entrusted his body to Naavagreen, this condition further strengthens that the patient's body is increasingly subdued through the beauty clinic. This study uses a qualitative research method with a case study approach. This research was conducted in May 2017. The research location was taken at the Naavagreen Natural Skincare Beauty Clinic in Kotabaru, Yogyakarta. There were four informants who were interviewed. The concept of analysis uses Michael Foucault's thinking about the birth of clinic as well as power and knowledge. The results of this study are that the power relationship between doctors and patients is dominated by doctors who have legitimacy in subduing the patient's body (skin and face) to follow the recommended treatment. Patients are dominated to follow it, even patients become a means of spreading power over the knowledge of Doctors and Naavagreen institutions (beauty specialists) about the beautiful concept offered by Naavagreen. Patients are disciplined by Doctors or Naavagreen. Naavagreen is able to differentiate between naturally beautiful, clean people from people who do not meet the criteria for beauty for Naavagreen. The beautiful construction of Naavagreen's version is getting more complete and more accommodating people's expectations about beauty that must be fulfilled by everyone.